Response To Infusion Of Polyelectrolyte Fractionated Human Factor VIII Concentrate In Human Haemophilia A - Kernoff, P B A; Lane, R S; Middleton, S; Tuddenham, E G D (Thrombosis and Haemostasis, 1981)
Plasma fractionation using polyelectrolytes (PEs) has potential advantages which include simplicity of procedure, high product purity, increased yield and removal of hepatitis viruses. The purpose of this study was to assess the in-vivo response to PE-fractionated human factor VIII concentrate (PE VIII) given to 3 volunteers with severe haemophilia A. PE VIII fractionated from bulk cryo- precipitate had a high specific activity (6.74 u/mg protein), no detectable isoagglutinins, a low fibrinogen content, high ratio of VIII coagulant activity (VIII:C)to VIII-related antigen (VIIIR:Ag), and a ratio of VIII:C to VIII coagulant antigen (VIII:CAg) of approximate unity. Single infusions, each of about 2000 i.u.(25 - 40 i.u./kg), were administered i.v. over 10 mins. There were no clinical, haematological or biochemical adverse effects during the 48 hr. post-infusion observation period. Immediate post-infusion recoveries of VIII:C were 119, 102 and 70 per cent with late phase half disappearance times of 17, 19 and 17 hours respectively. These values were similar to those obtained after infusion of intermediate-purity factor VIII concentrate to the same patients, and are in accord with the results of previous studies using conventional concentrates. PE VIII has potential as a therapeutic material for patients with haemophilia A.